Place-Based Arts Engagement and Learning Histories: An Effective Tool for Climate Action - Smith, Kate; McDonagh, Briony; Brookes, Ed (Environmental Communication)
Artistic works informed by the global climate emergency are now common. Yet research typically focuses on the role of art in climate communication, rather than evaluating opportunities for large-scale public art to drive climate action and behavioral change amongst audiences. Indeed, arts, culture, and heritage are poorly integrated into Action for Climate Empowerment (ACE) even though understanding whether, and how, art drives community engagement with climate issues is crucial for pursuing meaningful adaptation and resilience strategies. This paper addresses these research gaps, drawing on the evaluation of FloodLights, a series of multimedia art installations exploring experiences of living with water past/present/future in Kingston-Upon-Hull, UK, shown in October 2021. Key findings demonstrate that FloodLights empowered audience members to engage in climate and water action. Emotional responses to the installations drove engagement amongst audience members and inspired behavior change. Feedback from respondents demonstrates specific ways in which increased awareness of water and flooding issues is coupled with tangible connections to family and community. We demonstrate that arts-based interventions are effective in raising climate awareness and changing behaviors, and demonstrate that local communities have profound connections to their watery histories and identities, driving even greater impact in the future.
Keywords: Climate change communication; Arts and heritage; Place-based; Action for climate empowerment' Flooding and flood risk